Avian haematology and biochemistry 2. Biochemistry. Issue 3 (5th March 2015) - Sabater, Mikel; Forbes, Neil
Abstract : Birds typically hide signs of disease until pathogenesis is advanced. Haematology and biochemistry can help with diagnosis. This article, the second in a two‐part series, considers what can be learned from biochemistry, discussing each of the analytes in turn. The first article, published in the November/December issue of In Practice (Sabater and Forbes 2014), discussed haematology.